Determination of Common Antipsychotics in Quantisal-Collected Oral Fluid by UHPLC-MS/MS: Method Validation and Applicability for Therapeutic Drug Monitoring. Issue 1 (February 2016) - Patteet, Lisbeth; Maudens, Kristof E.; Morrens, Manuel; Sabbe, Bernard; Dom, Geert; Neels, Hugo
Abstract : Background: Oral fluid (OF) is an interesting alternative for conventional blood testing in therapeutic drug monitoring. OF can be used for screening but its value for quantification has to be established. Methods: To evaluate the value of OF for quantification of 11 commonly used antipsychotics (APs) and 5 metabolites, an ultra-high performance liquid chromatography-tandem mass spectrometric method was validated. OF was obtained from psychiatric patients using a Quantisal collection device. OF to serum concentration ratios were determined, taking into account the exact volume of collected OF. Results: Linearity was evaluated at 7 or 8 calibration levels. Accuracy criteria were fulfilled, except for pipamperone (PIP) at quality control (QC) low. The intraday precision ranged 0.88%–14.73% and interday precision ranged 1.92%–16.17%. The mean recovery from the collection pad was 37.1% at QC low and 40.3% at QC high for 1 mL of collected OF; for 0.5 mL collected OF mean recovery was 35.0% at QC low and 37.3% at QC high. When 0.1 mL OF was collected, recovery data were unreliable. Mean absolute matrix effect was 101.1% (82.0%–120.0%). OF patient samples (n = 89) containing 269 APs and metabolites were acquired and the mean volume of collected OF was 0.562 mL (0.057–1.232 mL). The OF to serum ratios were above 1 for all APs (1.54–28.50), except for aripiprazole (0.21) and zuclopenthixol (0.66). A broad range of calculated ratios for all APs was obtained. Conclusions: This validated ultra-high performance liquid chromatography-tandem mass spectrometric method can be used to reliably quantify APs in OF, even when recovery is low. Because the correlation between OF and serum concentrations was low and in addition results were highly variable, it can only be concluded that OF is a potentially interesting matrix, particularly for screening for noncompliance. Abstract : Supplemental Digital Content is Available in the Text.